2004
DOI: 10.1038/sj.bjc.6602279
|View full text |Cite
|
Sign up to set email alerts
|

Atypical cancer pattern in patients with Parkinson's disease

Abstract: Among 14 088 patients, with a primary diagnosis of Parkinson's disease during the period 1977 -98 identified from the National Register of Patients, 1282 cancers were subsequently recorded in the Danish Cancer Registry, compared with 1464 expected, with a standardised incidence ratio (SIR) of 0.88 (95% confidence interval (CI), 0.8 -0.9). Significantly reduced risks were found for smokingrelated cancers, for example, cancers of the lung (SIR, 0.38), larynx (0.47) and urinary bladder (0.52), although moderate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
199
8
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(221 citation statements)
references
References 20 publications
12
199
8
2
Order By: Relevance
“…Although overall cancer risk among PD cases was lower in several studies, a relatively consistent finding was increased risk of melanoma [596,597,604,605,608]. In some studies, higher frequency of non-melanoma skin cancer [603,604] and breast cancer [600,604,605] was also reported.…”
Section: Cancermentioning
confidence: 89%
See 2 more Smart Citations
“…Although overall cancer risk among PD cases was lower in several studies, a relatively consistent finding was increased risk of melanoma [596,597,604,605,608]. In some studies, higher frequency of non-melanoma skin cancer [603,604] and breast cancer [600,604,605] was also reported.…”
Section: Cancermentioning
confidence: 89%
“…In some studies, higher frequency of non-melanoma skin cancer [603,604] and breast cancer [600,604,605] was also reported. Based on experimental evidence, a potential link between PD and melanin was suggested in the 1980s [609].…”
Section: Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, large cohorts of patients with PD show a slight but statistically significant and reproducible excess risk of specific cancers, particularly breast cancer (standardized incidence ratio 1.24, 95% CI ¼ 1.0-1.5), (70,71) an observation that may be partly explained by parkin deficiency in a subset of patients. The reduced expression of another PD-associated gene, pink1, in certain cancers and its possible regulation by the tumor suppressor gene PTEN (72,73) suggests that the dual roles of tumor suppression and neuroprotection may extend to other PD-associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, two studies have recently demonstrated a small but significant increased relative risk for malignant melanoma and other nonmelanotic skin cancers in PD, but probably not related to LD. 26,27 It is recommended that PD patients be monitored regularly for skin cancer, but a history of melanoma should not preclude the use of LD.…”
Section: Safety Issues: Malignant Melanomamentioning
confidence: 99%